Nonfatal Drowning in People with Parkinson's Disease - Queiroga, AC (2020)
We read with great interest the recent case report by Tosserams and colleagues on a 56-year-old proficient swimmer and the decline in his swimming abilities attributed to Parkinson's disease. We also appreciate the earlier article by Neves and colleagues on the risk of drowning in people with Parkinson's disease. We applaud the authors for raising awareness of drowning as a consequence of a decline in swimming abilities, particularly in the context of Parkinson's disease. Our concern, and reason for corresponding, is the continued use of outdated terminology in the title and text of both articles, namely the term near drowning.